Growth pattern for body weight, body length and height at withers of Kalahari Red goats - Rosali, Mohamad Hifzan; Idris, Ismail; Yaakub, Halimatun (2015)
The objective of this study was to determine the body weight, body length and height at withers of Kalahari Red goats raised under semi-intensive grazing system. Body weight and body measurements of Kalahari Red goats were obtained from 192 goats at MARDI Research Station, Kluang, Johor and analyzed according to age from birth to 48 months. The result showed that Kalahari Red goats had a constant growth rate up to 48 months of age. Animals with longer body length and higher withers height had heavier body weight compared to animals that were short in length and height. The highest correlation coefficient was between body weight and height at withers (r=0.96). The body measurements are important as indicators in establishing breed parameters for genetic improvement in the tropical country like Malaysia.